Rancangan Explosive Detector Untuk Mengetahui Keberadaan Serta Jenis Bahan Peledak Dengan Membandingkan Besar Nilai Medan Magnet Menggunakan Arduino - Yuyun Suprapto; M. Erwin Zakariya K. (Jurnal Penelitian)
This design was created as an alternative Explosive Detector equipment as well as provide additional help if at an airport not provided the proper equipment. Its equipment is not yet available Explosive Detector at some airport and its equipment is expensive, the writer wanted to make a design Explosive Detector with a low costand designed with the latest technology. The design of Explosive Detector capable of detecting the presence and type of explosives by calculating a large magnetic field as well as large comparing magnetic field so they will know what kind of explosives were detected. The draft Explosive Detector uses Magnetometer sensor as the basic concept.